Sentimen Analisis & Topik Modeling menggunakan Latent Semantik Indexing (Studi Kasus: Aplikasi Detikcom) - Glenzkovic Samuel Moniharapon; Dedi Iskandar Inan; Ratna Juita; Victor Arie Lambadya Sirait (Universitas Islam Raden Rahmat, Malang, 2024)
The proliferation of digital news platforms has transformed information consumption, making user experience (UX) a key success factor for Detik.com, a leading news application in Indonesia. This research aims to explore the relationship between UX and news through sentiment analysis and topic modelling. The methods include web scraping for data collection, descriptive analysis for sentiment, and Latent Semantic Indexing (LSI) for topic modelling. Out of 14,320 reviews analyzed, 45.6% were positive, focusing on the speed of updates and news quality. Conversely, 41.18% of reviews were negative, highlighting disruptive ads and login issues, while 13.76% were neutral. LSI identified eight main topics, including user experience and ad complaints. Visualizations through heatmaps, distance maps, and word clouds emphasized terms like